DECODING DIPLOMATIC TRANSLATION: STRATEGIES FOR TRANSLATING COMPLEX SENTENCES - Sattarova Nodira Musurmonovna (Ethiopian International Journal of Multidisciplinary Research, 2025)
Diplomatic translation is one of the most nuanced and intricate fields in translation studies. It deals with complex sentence structures, formal language, and ambiguous expressions that require careful interpretation to ensure clarity and accuracy. Translators working in this domain face challenges that extend beyond language, such as understanding political, cultural, and historical contexts. This article explores the strategies required for decoding and translating complex sentences in diplomatic texts. It emphasizes breaking down sentence structures, analyzing intent, adapting to cultural differences, and ensuring formality in tone. By employing these strategies, translators can achieve high levels of accuracy and professionalism, contributing to effective international communication.